Getting Everyone Onboard: Framing Collective Goal Progress Broadens Participation in Collective Marketing Campaigns - Kim, Yaeeun; Reeck, Crystal (Frontiers in Psychology, 2019)
Collective marketing campaigns may feature goals that are not shared equally by all customers, such as a fundraiser for an environmental cause. For such campaigns, how can marketers encourage broad participation? The present research demonstrates that the framing of collective progress in such campaigns can broaden participation by highlighting the “large area” of progress towards the goal, emphasizing progress achieved for campaigns in their late stages and progress remaining in their early stages. We tested this large area hypothesis in the context of a waste reduction drive, examining the reactions of Republicans and Democrats who might be more or less inclined to support the drive respectively. Study 1 examined these processes when the drive was nearing completion, finding that an accumulating frame (focusing on progress achieved) increased motivation to participate for Republicans to levels comparable with Democrats. Study 2 evaluated these processes at earlier stages in the drive’s progress. In these circumstances, a remaining frame (focusing on contributions still needed) increased motivation to participate among Republicans to a similar level as Democrats. These findings indicate framings that highlight the large area in collective progress broaden participation in collective marketing campaigns, suggesting that marketers should highlight remaining contributions needed early on and accumulated contributions received later in collective marketing campaigns.